BUILDING LEARNING COMITMENT DAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH - Sukawi, Zainal (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2013)
This article explores the importance of building commitment to learning and learning strategies in Islamic Religious Education (PAI) in schools. In the context of modern education, PAI faces the challenge of remaining relevant and effective in shaping students' character and spirituality. This study highlights the main principles that must be integrated in PAI learning design, including the integration of Islamic values ​​with modernity, the use of Islamic educational technology, and an active and reflective learning approach. In addition, this article discusses the importance of inclusivity and moderation in PAI learning to create a conducive learning environment for all students. Using a comprehensive literature approach, this article identifies implementation challenges and offers strategies to increase the effectiveness of PAI, such as developing responsive curricula and increasing teacher competency. In conclusion, effective PAI learning requires an adaptive and responsive approach to changing times while still maintaining the essence of Islamic teachings.